Value of delayed-enhancement cardiovascular magnetic resonance imaging in predicting myocardial viability after surgical revascularization. - Selvanayagam, J; Kardos, A; Francis, J; Wiesmann, F; Petersen, SE; Taggart, D; Neubauer, S (2004)
BACKGROUND: Despite the accepted utility of delayed-enhancement MRI in identifying irreversible myocardial injury, no study has yet assessed its role as a viability tool exclusively in the setting of coronary artery bypass surgery (CABG), and no study has repeated delayed-enhancement MRI late after revascularization. In a clinical trial in which patients underwent CABG by either the off-pump or on-pump surgical technique, we hypothesized that (1) preoperative delayed-enhancement MRI would have high diagnostic accuracy in predicting viability and (2) the occurrence of perioperative myocardial necrosis would affect late regional wall motion recovery. METHODS AND RESULTS: Fifty-two patients undergoing multivessel CABG were studied by preoperative and early (day 6) and late (6 months) postoperative cine MRI for global and regional functional assessment and delayed-enhancement MRI for assessment of irreversible myocardial injury. Preoperatively, 611 segments (21%) had abnormal regional function, whereas 421 segments (14%) showed evidence of hyperenhancement. At 6 months after revascularization, 57% (343 of 611) of dysfunctional segments improved contraction by at least 1 grade. When all preoperative dysfunctional segments were analyzed, there was a strong correlation between the transmural extent of hyperenhancement and the recovery in regional function at 6 months (P<0.001). Of a total of 96 previously dysfunctional but nonenhancing or minimally hyperenhancing myocardial segments that did not improve regional function at 6 months, 35 (36%) demonstrated new perioperative hyperenhancement in the early postoperative MRI scan. CONCLUSIONS: Delayed-enhancement MRI is a powerful predictor of myocardial viability after surgery, suggesting an important role for this technique in clinical viability assessment.